ChemInform Abstract: Facile Synthesis of Thieno[2, 3‐d]pyrimidine Derivatives Using Inorganic Base Catalysis. Issue 43 (21st October 2014) - Meng, Shuangming; Jia, Zhifang; Wang, Kewei; Fan, Yueqin; Guo, Yong
Abstract A facile and efficient synthesis of thienopyrimidine derivatives (IV) via reaction of carbodiimide derived from iminophosphorane (I) with secondary amines is developed using potassium carbonate as inorganic base catalyst.